Etude lexicographique et discursive des collocations en vue de leur intégration dans une base de données terminologiques - Mojca Pecman (JoSTrans: The Journal of Specialised Translation)
In this paper we propose a discursive analysis of collocations with a view to improving a lexicographical approach to this type of linguistic items within an online terminological database, known as the ARTES database (Aide à la Redaction de TExtes Scientifiques / Dictionary-assisted writing tool for scientific communication). The target users of this database are specialised translators and scientists who need to write academic papers in their second language. Collocations can provide useful information about the way terms are used in Languages for Special Purposes. The paper discusses a number of lexicographical issues raised by such a project: namely the difficulty in distinguishing domain-specific collocations from genre-specific collocations when building up phraseological resources. In order to shed light on this problem, we conduct a discursive analysis of the most salient collocational phenomena observed in a corpus of scientific articles from the field of Earth and Planetary Sciences, Environmental Sciences and Ecology. The corpus that was compiled consists of texts organised according to the structure of scientific articles, allowing for the distributional analysis of collocations across texts. This study opens up routes to an interpretation of the behaviour of collocations according to their specific roles within a genre, discourse, domain and text.